Partai Islam dan Pemilih Islam di Indonesia - Romli, Lili (Pusat Penelitian Politik, 2004)
The resurgent o f Islamic parties occurs in the reform era because o f many factors which are theological, sociological, historical, reformation and democratization. Unfortunately the resurgent of Islamic parties cannot be endorsed by the Islamic voters. This can be seen from a small and unsignificant vote reached by the Islamic parties. In the 1999 general election, the Islamic parties only have !7,8 percent vote and in the 2004 general election only have 21,17percent vote. This small and unsignificant vote o f the Islamic parties happened because o f fragmentation o f Islamic parties and ideological orientation change o f Islamic voters.